(untitled) (International Journal of Innovative Technologies in Economy, 2022)
The article examines the evolutionary development of the concepts «security», «economic security» and «economic security of the enterprise». The types of internal and external threats are analyzed. The evolution and definition of the concept are considered, the components of economic security, risks and main goals of economic security of enterprises are derived. It was determined that the concept of «economic security» allows us to understand that modern enterprises, being in various situations, are forced to make risky decisions to prevent threats and dangers. The concept of «economic security of the enterprise» is characterized. It was determined that the economic security of the enterprise is an extremely deep concept. In the most general form, it can be characterized as the absence of various dangers and threats, which, obviously, is hardly possible in the world. The concept of economic security of enterprises is generalized and a more precise definition is given, where it is indicated that the economic security of an enterprise is a system that provides the possibility of preventing various threats and as a result of neutralizing these threats, it protects the economic interests of the enterprise and prevents losses above the critical limit.